Fuzzy logic and multi-dimensional wavelet transform based robust watermarking for depth image based rendering 3D images - Abbasi, A. (2014)
With the advancement in the processing capabilities of computers, the use of three dimensional objects (3DObjects) in different field has been increased in recent years. Moreover the cost of 3D display devices has also become cheaper. Depth Image Based Rendering (DIBR) of a 3D image is a 3D image representation consisting centre image and depth image. In this paper a watermarking scheme is proposed in Multi-dimensional wavelet transformation (MDWT) to protect the 3D data of DIBR 3D images. We tried to embed the watermark in the center image such that it should be kept in the left image and right image after the rendering operation. Interval Type-2 Fuzzy Logic System (IT2FLS) is used for data fusion and build a Model for spatial masking in wavelet domain. Masking modeling is complicated task and no single theoretical formulation to precisely compute the perceptual value for corresponding wavelet coefficient. The fuzzy input variables noise visibility and entropy are calculated for each wavelet coefficients. The output of the fuzzy system is a single value which gives a perceptual value for each corresponding wavelet coefficient. The experimental results show that the proposed technique is robust as well as imperceptible as watermark is retained in the rendered left and right images. Moreover, the bit error rate of the extracted watermark approaches to 0. The proposed technique embed watermark with least distortion and it is robust to JPEG compression, depth image alteration, Gaussian noise and rotation attacks.